Business planning in nonprofit: Laying the ground for customer relationship management in Instituto de Empreendedorismo Social - Quaresma, Martim Pardal Agarez (2013)
A Work Project, presented as part of the requirements for the Award of a Masters Degree in Management from the NOVA – School of Business and Economics